Digital Distribution as~an E‑commerce Sales Channel - Dagmara Skurpel (Comparative Economic Research. Central and Eastern Europe, 2022)
In a matter of decades, digital technologies have transformed the way we communicate with others, conduct business, produce goods and services, as well as the way we live, work, and spend our spare time. These, often rapid, developments hold a lot of promise for the future, in terms of wealth generation, technological advances, and improving the quality of life. At the same time, they also bring challenges associated with a lack of skills, new and fast-emerging markets, consumer protection, industrial re-organization, trust, security, and privacy. The private life of society, as well as the world of business, have moved to the virtual world. The transformation to e-business is complex, and to be successful, a balance needs to be struck between strategy, a customized business model, the relevant processes, and the technology used. The aim of the article is to present the essence of digital distribution and the key factors in the dynamics of its development. Secondary data on the development of digital distribution in the world and in Europe over the past 20 years are presented, and the forecasts for the coming years are calculated.
Keywords: L81; M39; D12; 330; digital distribution; e-commerce; sales channel; digital product